RNAI-MEDIATED SILENCING OF MATRIX METALLOPROTEINASE 1 IN EPIDERMAL KERATINOCYTES INFLUENCES THE BIOLOGICAL EFFECTS OF INTERLEUKIN 17A - J. A. Mogulevtseva; A. V. Mezentsev; S. A. Bruskin (Вавиловский журнал генетики и селекции)
Matrix metalloproteinases (MMPs) are important for the pathogenesis of psoriasis and other autoimmune disorders. In the extracellular matrix, accumulation of proinflammatory cytokines, such as interleukin 17A (IL-17A), leads to induction of several MMPs, including MMP1. MMPs change the composition and other properties of the extracellular matrix. These changes facilitate tissue remodeling and promote the development of psoriatic plaques. The aim of this study was to explore how MMP1 silencing might influence the biological effects of IL-17A on migration and proliferation of human epidermal keratinocytes and the expression of genes involved in their division and differentiation. The experiments were performed with MMP1-deficient and control epidermal keratinocytes, HaCaT-MMP1 and HaCaT-KTR, respectively. Cell proliferation and migration were assessed by comparative analysis of the growth curves and scratch assay, respectively. To quantify cell migration, representative areas of cell cultures were photographed at the indicated time points and compared to each other. Changes in gene expression were analyzed by real-time PCR. The obtained results demonstrated that MMP1 silencing in the cells treated with IL-17A resulted in downregulation of MMP9 and -12, FOSL1, CCNA2, IVL, KRT14 and -17 as well as upregulation of MMP2, CCND1 and LOR. Moreover, MMP1 silencing led to a decrease in cell proliferation and an impairment of cell migration. Thus, MMP1-deficiency in epidermal keratinocytes can be beneficial for psoriasis patients that experience an accumulation of IL-17 in lesional skin. Knocking MMP1 down could influence migration and proliferation of epidermal keratinocytes in vivo, as well as help to control the expression of MMP1, -2, -9 и -12, CCNA2, CCND1, KRT14 and -17 that are crucial for the pathogenesis of psoriasis.